PEMANFAATAN MEDIA PEMBELAJARAN PUZLLE UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV PADA PELAJARAN IPAS - Triana Sari; Veryliana Purnamasari; Endang Wuryandini (STKIP Subang, 2023)
This study aims to determine the positive effect of the use of puzzle learning media in improving student learning outcomes in class IV lessons IPAS at SDN Rejosari 01 Semarang. This research is quantitative. The research method used is a Pre-Experimental Design type of One-Group Pre-test Post-test Design. The sample in this study amounted to 25 people. The instruments used in this study were tests and documentation. The results of this research classically show that the average post-test score of students increases after using the puzzle learning media compared to the average pre-test score. The data analysis technique used is pared samples t-test analysis with the help of the SPSS program version 22.0. The results of the study showed sig = 0.000 ≤ 0.05, so it was said that there was a significant difference between the results of the pre-test and post-test. In addition, the N-Gain test shows that a percentage of 0.66 is included in the quite effective category. So that this proves that the use of puzzle learning media influences improving student learning outcomes in learning IPAS materials for class IV SDN Rejosari 01 Semarang.